Recent advances in the design of implantable insulin secreting heterocellular islet organoids - Akolpoglu, M. Birgul (2021)
Islet transplantation has proved one of the most remarkable transmissions from an experimental curiosity into a routine clinical application for the treatment of type I diabetes (T1D). Current efforts for taking this technology one-step further are now focusing on overcoming islet donor shortage, engraftment, prolonged islet availability, post-transplant vascularization, and coming up with new strategies to eliminate lifelong immunosuppression. To this end, insulin secreting 3D cell clusters composed of different types of cells, also referred as heterocellular islet organoids, spheroids, or pseudoislets, have been engineered to overcome the challenges encountered by the current islet transplantation protocols. β-cells or native islets are accompanied by helper cells, also referred to as accessory cells, to generate a cell cluster that is not only able to accurately secrete insulin in response to glucose, but also superior in terms of other key features (e.g. maintaining a vasculature, longer durability in vivo and not necessitating immunosuppression after transplantation). Over the past decade, numerous 3D cell culture techniques have been integrated to create an engineered heterocellular islet organoid that addresses current obstacles. Here, we first discuss the different cell types used to prepare heterocellular organoids for islet transplantation and their contribution to the organoids design. We then introduce various cell culture techniques that are incorporated to prepare a fully functional and insulin secreting organoids with select features. Finally, we discuss the challenges and present a future outlook for improving clinical outcomes of islet transplantation.